Improved Efficiency of All-Inorganic Quantum-Dot Light-Emitting Diodes via Interface Engineering - Xu, Qiulei; Li, Xinyu; Lin, Qingli; Shen, Huaibin; Wang, Hongzhe; Du, Zuliang (Frontiers in Chemistry, 2020)
As the charge transport layer of quantum dot light-emitting diodes (QLEDs), metal oxides are expected to be more stable compared with organic materials. However, the efficiency of metal oxide based all-inorganic QLEDs is still far behind that of organic-inorganic hybrid ones. The main reason is the strong interaction between metal oxide and QDs leading to the emission quenching of QDs. Here, we demonstrated NiOx-based all-inorganic QLEDs with a maximum current efficiency of 20.4 cd A-1 and external quantum efficiency (EQE) of 5.5%, which is among the most efficient all-inorganic QLEDs. The high efficiency is mainly attributed to the Al2O3 deposited at the NiOx/QDs interface to suppress the strong quenching effect of NiOx on the QD emission, together with the MoOx that reduced the leakage current and faciliated hole injection, more than 300% enhancement was achieved compared with the pristine NiOx based QLEDs. Our study confirmed the effect of decorating the NiOx/QDs interface on the performance enhancement of the all-inorganic QLEDs.